A Detailed, Multi‐Scale Assessment of an Atmospheric River Event and Its Impact on Extreme Glacier Melt in the Southern Alps of New Zealand. Issue 9 (2nd May 2021) - Kropač, Elena; Mölg, Thomas; Cullen, Nicolas J.; Collier, Emily; Pickler, Carolyne; Turton, Jenny V.
Abstract: North‐westerly airflow and associated atmospheric rivers (ARs) have been found to profoundly influence New Zealand's west coasts, by causing flooding, landslides and extreme ablation and accumulation on glaciers in the Southern Alps. However, the response of local glacier mass balance to synoptic‐scale circulation, including events with ARs, has typically not been investigated by considering mesoscale processes explicitly. In this study, high‐resolution atmospheric simulations from the Weather Research and Forecasting model are used to investigate the mesoscale drivers of an extreme ablation event on Brewster Glacier (Southern Alps), which occurred on February 6, 2011 during the landfall of an AR on the South Island. The following processes were found to be crucial for transferring the high temperature and water vapor contained in the AR into energy available for melt on Brewster Glacier: First, the moist‐neutral character of the air mass enabled the flow to pass over the ridge, leading to the development of orographic clouds and precipitation on the windward side of the orography, and foehn winds on the leeside. These processes fueled melt through longwave radiation and strong turbulent and rain heat fluxes within the high‐condensation environment of the orographic cloud. Second, orographic enhancement occurred due to both cellular convection within the cloud and the combined effect of multiple precipitating systems by the seeder‐feeder‐mechanism. These results indicate the potential importance of AR dynamics for New Zealand's glaciers. They also illustrate the benefit of mesoscale atmospheric modeling for advancing process understanding of the glacier‐climate relationship in New Zealand. Plain Language Summary: Atmospheric rivers, which are elongated, narrow structures in the atmosphere that convey large amounts of moisture through the midlatitudes, have been found to impact coastal regions worldwide, including New Zealand. Besides causing flooding and landslides, they can affect glaciers in coastal mountains such as the Southern Alps. The processes causing the high temperature and moisture in atmospheric rivers to trigger melt (or snowfall) at the glacier surface have, however, not been investigated explicitly because they operate at the size of mountain valleys and ridges which are difficult to represent in global data‐sets. We address this by using an atmospheric model with high spatial detail to simulate a case study, where an atmospheric river coincided with extreme melt on Brewster Glacier in the Southern Alps. We find that the stability characteristics of the impinging warm and moist air masses lent the air the potential to ascend the mountain instead of being directed around. This resulted in cloud and precipitation development on the windward slopes whereby rain amounts were further enhanced by internal processes within the clouds. Melt was promoted through heat released from condensation and rainfall. Conversely, on the lee slopes, downslope winds caused warm and dry conditions. Key Points: The mass balance of Brewster Glacier is affected by an atmospheric river causing extreme melt through rain and turbulent energy transfer Orographic enhancement and weak stability in the atmospheric river cause precipitation on windward slopes while leesides are foehn‐affected Regional atmospheric modeling can advance the process understanding of the glacier‐climate relationship in New Zealand's mountains